2001
DOI: 10.1152/ajpgi.2001.280.6.g1314
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation, apoptosis, NF-κB expression, enzyme, protein, and weight changes in livers of burned rats

Abstract: Thermal injury has been shown to alter gut epithelium and heart myocyte homeostasis by inducing programmed cell death. The effect of thermal injury on hepatocyte apoptosis and proliferation, however, has not been established. The purpose of this study was to determine whether a large thermal injury increases liver cell apoptosis and proliferation and whether these changes were associated with alterations in hepatic nuclear factor kappaB (NF-kappaB) expression and changes in liver enzymes and amount of protein.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 19 publications
3
62
0
Order By: Relevance
“…Immediately after burn, the damage of the liver may be associated with an increased hepatic edema formation. We (15) have shown that the liver weight and liver/ bodyweight significantly increased 2 to 7 days after burn when compared with controls. As hepatic protein concentration was significantly decreased in burned rats, we suggest that the liver weight gain is due to increased edema formation rather than increases in the number of hepatocytes or protein levels.…”
Section: Hepatic Changes In Response To a Burn And The Hepatic Acute mentioning
confidence: 65%
See 2 more Smart Citations
“…Immediately after burn, the damage of the liver may be associated with an increased hepatic edema formation. We (15) have shown that the liver weight and liver/ bodyweight significantly increased 2 to 7 days after burn when compared with controls. As hepatic protein concentration was significantly decreased in burned rats, we suggest that the liver weight gain is due to increased edema formation rather than increases in the number of hepatocytes or protein levels.…”
Section: Hepatic Changes In Response To a Burn And The Hepatic Acute mentioning
confidence: 65%
“…Liver damage has been associated with increased hepatocyte cell death (15). In general, cell death occurs by two distinctly different mechanisms: programmed cell death (apoptosis) or necrosis (30).…”
Section: Hepatic Changes In Response To a Burn And The Hepatic Acute mentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear factor kappa B (NF-kB) is a transcriptional factor that plays a key role in inflammation and tissue damage, in the regulation of cell proliferation and apoptosis in human hepatic cells (8). It regulates the expression of multiple inflammatory genes, stressinduced responses, and survival (9).…”
mentioning
confidence: 99%
“…The liver plays an important role in metabolism, inflammation, homeostasis and host defence mechanisms (Klein et al 2004), and is a major organ responsible for initiating multiorgan dysfunction syndrome (MODS) following burn injury. The mechanism of burn-induced injury is not completely understood; however, several mechanisms, including hypoxia, free radicals, inflammation, and apoptosis are thought to be involved (Jeschke et al 2001). The excessive production of free radicals such as superoxide anion, hydrogen peroxide and hydroxyl radicals as well as the occurrence of lipid peroxidation products such as malondialdehyde (MDA) due to oxidative stress are associated with burn-induced liver dysfunction (Horton 2003;Bekyarova et al 2009;Bekyarova et al 2012).…”
mentioning
confidence: 99%